The Impact of Left Ventricular Assist Device Infections on Postcardiac Transplant Outcomes: A Systematic Review and Meta-Analysis. Issue 8 (November 2019) - Chahal, Daljeet; Sepehry, Amir A.; Nazzari, Hamed; Wright, Alissa Jade; Toma, Mustafa
Abstract : Left ventricular assist devices (LVADs) are associated with numerous short- and long-term complications, including infection. The impact LVAD infections have on clinical outcomes after transplantation is not well established. We sought to determine whether the presence of infection while on LVAD support negatively influences outcomes after cardiac transplantation. We searched electronic databases and bibliographies for full text studies that identified LVAD infections during support and also reported on posttransplant outcomes. A meta-analysis of posttransplant survival was conducted using a random effects model. Of 2, 373 records, 13 bridge to transplant (BTT) cohort studies were selected (n = 6, 631, 82% male, mean age 50.7 ± 2.7 years). A total of 6, 067 records (91.5%) received transplant. There were 3, 718 (56.1%) continuous-flow LVADs (CF-LVADs), 1, 752 (26.4%) pulsatile LVADs, and 1, 161 (17.5%) unknown type records. A total of 2, 586 records (39.0%) developed LVAD infections. Patients with LVAD infections were younger (50.5 ± 1.5 vs. 51.3 ± 1.5, p = 0.02), had higher body mass indeices (BMIs) (28.4 ± 0.7 vs. 26.8 ± 0.4, p < 0.01), and longer LVAD support times (347.0 ± 157.6 days vs. 180.2 ± 106.0 days, p < 0.01). Meta-analysis demonstrated increased posttransplant mortality in those patients who had an LVAD infection (hazard ratio [HR] 1.30, 95% CI: 1.16–1.46, p < 0.001). Subgroup meta-analyses by continuous-flow and pulsatile device type demonstrated significant increased risk of death for both types of devices (HR 1.47, 95% CI: 1.22–1.76, p < 0.001 and 1.71, 95% CI: 1.19–2.45, p = 0.004, respectively). Patients who develop LVAD infections are younger, have higher BMIs and longer LVAD support times. Our data suggests that LVAD-related infections result in a 30% increase in postcardiac transplantation mortality. Strategies to prevent LVAD infections should be implemented to improve posttransplant outcomes in this high-risk population. Abstract : Supplemental Digital Content is available in the text.